Family Matters: The Role of the Family in Immigrants' Destination Language Acquisition - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
This paper is concerned with the relationship among family members in the determinants of destination language proficiency among immigrants. A model of immigrant language proficiency is augmented to include dynamics among family members. It is tested using data on a sample of recent immigrants. Children are shown to have a negative effect on their mother?s language proficiency, but no effect on their father?s. There is a substantial positive correlation between the language skills of spouses. This is due to the correlation between spouses in both the measured determinants and the unmeasured determinants of destination language skills among spouses.
Keywords: J61; J24; J16; J15; 330; Immigrants; language skills; family; longitudinal data; Migranten; Sprache; Familiensoziologie; Schätzung; Australien